Color tunable emission and energy transfer in LaSi3N5:Ce3+, Tb3+ phosphors for UV white LEDs. Issue 2 (4th January 2017) - Du, Fu; Zhuang, Weidong; Liu, Ronghui; Liu, Yuanhong; Zhong, Jiyou; Gao, Pin; Zhang, Xia; Gao, Wei; Shao, Lengleng
Abstract : Tunable blue-green-emitting LSN:0.09Ce 3+, y Tb 3+ phosphors white-light UV LED. Abstract : A series of new blue-green emitting LaSi3 N5 :Ce 3+, Tb 3+ phosphors were obtained through a high temperature solid-state method. The crystal structure, photoluminescence properties and energy transfer from Ce 3+ to Tb 3+ were investigated. The doped ions Ce 3+ and Tb 3+ were confirmed to occupy the same crystallographic sites as La 3+ using a Rietveld structure refinement method. The emission spectra of these phosphors was composed of a blue emission band attributed to the d–f transition of Ce 3+, together with several sharp lines ascribed to the emission of Tb 3+ under UV light excitation. Thus a color tunable emission from blue to green was obtained via controlling the doping concentration of Tb 3+ . In addition, the mechanism of energy transfer, efficiency of energy transfer, chromaticity coordinates and thermal stability of these phosphors were investigated. The results indicated that the Ce 3+, Tb 3+ co-activated LaSi3 N5 phosphors with color-tunable blue-green emission and high quantum efficiency may have potential for UV white LEDs.